Examining Demographics and Perceived ‘Sense of Community’ of Social Media-Based Professional Learning Communities - Hensley, Matthew; Waters, Stewart; Kenna, Joshua L.; Russell, William (Research in Social Sciences and Technology, 2023)
Social media has undoubtedly shifted the landscape of educator professional development in the 21st century. The establishment and development of identifiable professional learning communities (PLCs) like the #SSChat social studies community on Twitter enables educators to connect and collaborate with other professionals across the globe from their own mobile device. The purpose of this study was to determine the demographic features of the #SSChat members. Moreover, we sought to determine if there were any significant differences in #SSChat member’s perceived ‘Sense of Community’ (SOC) based on those demographics. No statistically significant findings were discovered. Still, the demographic data provide good discussions.